Transcriptome profiling revealed salt stress-responsive genes in Lilium pumilum bulbs - So, Kyongsok; Pak, Unil; Sun, Shaoying; Wang, Yiping; Yan, Hao; Zhang, Yanni (Frontiers in Plant Science, 2022)
Lilium pumilum is an important ornamental, culinary and medicinal herb with salt tolerance. However, underlying molecular regulatory mechanisms governing salt tolerance is poorly understood, challenging the cultivation of high salt-tolerant lily varieties. Here, we performed transcriptome sequencing on the bulb organs under salt stress treatment for different time periods (2 and 12 h), analyzed differential gene expressed levels and then identified several key genes associated with salt stress tolerance. Total 51566 unigenes were obtained using de novo assembly in the bulb organs. Then, 4096 DEGs were found and functionally classified by GO and KEGG enrichment analysis. 958 DEGs were co-induced throughout the entire period of salt stress (0-12 h) and of them, NF-YB3 transcription factor showed the most intense upregulation among the differentially expressed transcription factors, further validated as a hub gene through co-expression network analysis. Besides, gene encoding the metallothionein type 2 protein which has functions of ion detoxification and ROS scavenging showed the highest expression level throughout entire periods of stress and the most intense upregulation degree upon stress. In addition, genes encoding vicilin like seed storage protein and bidirectional sugar transporter SWEET14 which may promote the osmolyte accumulation were also intensely upregulated. Furthermore, gene that encodes phytohormone signaling factors such as E3-ubiquitin protein ligases, PYL4 and protein phosphatase 2C showed intense differential expressions. Taken together, we identified important candidate genes associated with salt tolerance of the L. pumilum bulb organs that may provide the excellent basis for further in-depth salt tolerance mechanisms of the lily bulbs.